(untitled) (Archive of Conferences, 2021)
The problem of individual activism in educational practice is one of the most pressing issues. E.I. As Itelson writes in his article “On the Attitude of Students to Foreign Languages as an Academic Science,” “to arouse students’ interest in language, to have a conscious attitude to its study, because in this case not allowed".